Experimental investigation into the Impact of Cyclic High Low Pressure Water Immersion on the Pore structure and Mechanical properties of coal - Pi Zikun; Li Rui; Wang Yan; Xiong Jiawen; Li Jiayi; Zhang Yifu; Peng Bin (Scientific Reports)
Abstract The extraction of coal seams with high gas content and low permeability presents significant challenges, particularly due to the extended period required for gas extraction to meet safety standards and the inherently low extraction efficiency. Hydraulic fracturing technology, widely employed in the permeability enhancement of soft and low-permeability coal seams, serves as a key intervention. This study focuses on the high-rank raw coal from the No. 13 coal seam at Xinjing Mine, utilizing a vacuum pressure saturation system, low-field nuclear magnetic resonance (LF-NMR) testing, and uniaxial compression mechanical testing to investigate the changes in porosity and connectivity of coal samples under conditions of high-pressure continuous immersion and high-low pressure cyclic immersion. Additionally, the uniaxial compression mechanical properties of the coal under various experimental conditions were analyzed. The findings reveal that the porosity of coal samples subjected to high-pressure continuous immersion and high-low pressure cyclic immersion initially decreases slightly before increasing as the immersion cycle progresses. The maximum porosity enhancements observed were 1.55% and 2.93%, respectively, while the total connectivity increased by 19.07% and 24.79%, respectively. Furthermore, The peak stresses of the coal samples were found to be 1.23–1.65 times, 1.65–3.21 times, and 1.56–4.24 times greater than those of the atmospheric-pressure continuous immersion, high-pressure continuous immersion, and high- and low-pressure cyclic immersion samples, respectively. The cyclic application of high and low confining pressures was shown to significantly promote the development of pore structures and enhance pore connectivity, leading to a more pronounced deterioration in coal body strength. These results provide a theoretical foundation and practical support for the application of hydraulic fracturing to improve permeability and the use of water injection to suppress gas outflow in coal seams with high gas content and low permeability within coal mines.